How Far Is Digital Technology Utilized in Biology Learning? Profile and Challenges in Higher Education - Nur Aisyah Takdir; Nurkhaerat Alimuddin; Dian Aswita; Oriny Tri Ananda; Nur Aisyah Ainun (BIOCHEPHY: Journal of Science Education, 2026)
Digital technology utilization has become an essential component of biology learning in higher education as it supports more interactive, flexible, and student-centered learning processes. This study aimed to describe the profile of digital technology utilization in learning among lecturers of the Department of Biology, Faculty of Mathematics and Natural Sciences, State University of Makassar, based on students’ perceptions. The study employed a quantitative descriptive method with a survey approach involving 110 fourth-semester students from the Biology Education, Biology, and Biotechnology study programs selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using descriptive statistics, including mean scores and percentages. The results indicated that the utilization of digital technology was categorized as high, with an overall mean score of 4.14. The digital material delivery aspect obtained the highest score (4.35), while technology utilization in laboratory activities received the lowest score (3.68). It can be concluded that digital technology has been optimally utilized in biology learning; however, greater efforts are needed to enhance its application in practical laboratory activities.